Subjective Loneliness and Psychological Well-Being of Adolescents with High Aggressiveness - Buslaeva, E.L.; Vlasova, N.V. (Psihologiâ i pravo, 2025)
Context and relevance. The problem of the younger generation aggressiveness does not lose its relevance, as the tendency of cruelty and physical violence among young people is increasing. The aim of the study was to identify the features of subjective loneliness and psychological well-being in adolescents with a high aggression level. The hypothesis was based on the assumption that adolescents have specific experiences of subjective loneliness and psychological well-being, which have different levels and correlations of indicators, unlike their peers with low levels of aggression. Materials and methods. The sample consisted of secondary school students (N = 76) aged 16-18 years (M = 17, SD = 0.7062), 42 male/34 female. The following methods were used: "Bass-Perry aggression level questionnaire" BPAQ (adaptation and validation by S.N. Enikolopov, N.P. Cybulsky); "Personal aggressiveness and conflict" (E.P. Ilyin, P.A. Kovalev); "Differential questionnaire of loneliness experience", DOPO-3 (E.N. Osin, D.A. Leontiev); "Scale of psychological well-being" (K. Riff, adaptation by L.V. Zhukovskaya, E.G. Troshikhina). The results of the study revealed high values in terms of loneliness and low values in terms of well-being among people with a high level of aggression, in contrast to respondents with a low level of aggression. Differences in the relationships between aggression, loneliness, and psychological well-being were found in the two groups, and similar negative associations of problematic loneliness with positive relationships with others and general loneliness with psychological well-being in both groups. Conclusions. Adolescents with high and low levels of aggression have significant differences in all criteria of experiencing loneliness and psychological well-being. Aggression gives a stronger experience of loneliness and reduces the psychological well-being of the individual. Контекст и актуальность. Проблема агрессивности молодого поколения не теряет своей актуальности, поскольку возрастает тенденция проявления жестокости, физического насилия среди молодежи. Цель исследования состояла в выявлении особенностей субъективного одиночества и психологического благополучия у лиц юношеского возраста с высоким уровнем агрессивности. Гипотеза заключалась в предположении о том, что у лиц юношеского возраста существуют особенности переживания субъективного одиночества и психологического благополучия, которые имеют разные уровни и связи показателей, в отличие от их сверстников с низким уровнем агрессивности. Методы и материалы. Выборку составили учащиеся общеобразовательной школы (n = 76) в возрасте 16-18 лет (M = 17, SD = 0,7062), 42 юноши и 34 девушки. Были использованы методики: опросник уровня агрессивности Басса-Перри BPAQ (адаптация и валидизация С.Н. Ениколопова, Н.П. Цибульского); методика «Личностная агрессивность и конфликтность» (Е.П. Ильин, П.А. Ковалев); дифференциальный опросник переживания одиночества ДОПО-3 (Е.Н. Осин, Д.А. Леонтьев); опросник «Шкала психологического благополучия» (К. Рифф, адаптация Л.В. Жуковской, Е.Г. Трошихиной). Результаты исследования выявили высокие значения по показателям одиночества и низкие значения по показателям благополучия у лиц с высоким уровнем агрессивности, в отличие от респондентов с низким уровнем агрессивности. Обнаружены различия связей показателей агрессивности, одиночества и психологического благополучия в двух группах и схожие отрицательные связи проблемного одиночества с позитивными отношениями с окружающими и общего одиночества с психологическим благополучием в обеих группах. Выводы. Лица юношеского возраста с высоким и низким уровнем агрессивности имеют значимые различия по всем критериям переживания одиночества и психологического благополучия. Агрессивность дает более сильное переживание одиночества и снижает психологическое благополучие личности.